Flood simulation in the La Llanga river (Peru) using hydrological modeling with HEC-HMS and HEC-GeoRAS (Revista Ciencia Agraria, 2025)
Floods are a phenomenon with low predictability in inter-Andean valleys. This study was conducted on the La Llanga River, located in the northern region of Peru (Cajamarca – Celendín), a tributary of the Marañón River, within the middle course of the Andes Mountains. The HEC-HMS and HEC-GeoRAS programs were used to model flood events, considering a return period of 50 years. The main issues identified include the loss of crops, livestock, housing, and human lives, highlighting the need to implement hydrological modeling systems that support the development of early warning mechanisms and raise awareness among the population and farmers living in riparian zones. The research is quantitative, descriptive, and non-experimental in nature. A 5,066-meter stretch of the main riverbed was analyzed, between the confluence with the Saraus River and its mouth at the Grande River (Llanguat). Grid systems and cross sections were applied to identify critical areas with greater flood depth, flow width, and velocity. The model results indicated flow velocities of up to 4.89 m/s, flood widths of up to 188 meters, and discharges exceeding 400 m³/s, with sediment and rock transport. These events have a significant impact on agricultural lands and tourism activities near the riverbed. It is concluded that a detailed understanding of fluvial dynamics is essential to reduce risks and optimize land use in vulnerable areas.
Keywords: basin; flood; simulation; model; La Llanga River